MATHEMATICAL MODEL OF THE MOTION PALLET PROCESS ON BRAKE MAGNETIC TYPE ROLLER - I. A. Sharifullin; A. L. Nosko; E. V. Safronov (Вестник СибАДИ, 2020)
Introduction. One of the main elements of the safe operation of gravity roller conveyors used in pallet racks is a brake roller. The most promising design is the brake roller magnetic (eddy current) type. The operation principle of such rollers is based on the laws of electromagnetic induction and involves the braking of a conductor moving in a magnetic field, due to the interaction of eddy currents (or Foucault currents) arising in the volume of the conductor with an external magnetic field. However, in the market of warehouse shelving equipment, brake magnetic rollers are not widely used due to their high cost, which is primarily due to the lack of domestic designs and methods for their calculation. The aim of the work is to develop a mathematical model of the moving pallets process on a magnetic type brake roller.Materials and methods. The paper presented the theoretical study results on the development of a mathematical model of the moving pallets process on a magnetic type brake roller, described in works on centrifugal friction rollers and eddy current brake devices.Results. The main parameter determining the functions of the brake magnetic roller and hence the speed of the pallet along the gravity roller conveyor is a magnetic viscosity coefficient. The speed dependence of the pallets on the brake magnetic roller for various values of a magnetic viscosity coefficient is determined, its analysis is carried out.Conclusions. A mathematical model of the moving pallets process on a brake magnetic roller is developed. The movement speed equation of the pallets on the brake magnetic roller is obtained. For a reasonable choice of the design parameters of the magnetic brake roller, experimental studies are required to determine a magnetic viscosity coefficient.